Teaching Factory Management Strategy to Increase Graduate Absorption at SMK Negeri 1 Godean, Sleman - Betty Mayasari; Rahmat Mulyanto; Saryanto Saryanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The high unemployment rate in Indonesia may be attributed to the mismatch between the competencies possessed by the workforce and the competencies required by the labor market, as well as the limited availability of job opportunities to accommodate all school graduates entering the workforce. Implementing a teaching factory management strategy is meant to improve vocational school graduates' skills to meet business and industry needs, making the Indonesian workforce more competitive. The teaching factory management functions are implemented and organized based on partnerships between vocational schools and industries, particularly those in the surrounding areas, through planning, implementation, evaluation, and supervision stages. This study employs a descriptive qualitative research design. Data collection techniques include participant observation, in-depth interviews, document analysis, and triangulation. The teaching factory management strategy at SMK Negeri 1 Godean has successfully improved students' work readiness by integrating academic learning with real-world industrial practices. Data indicates a significant increase in the absorption of graduates into the workforce, with the percentage of graduates directly employed rising from 29.5% in 2021 to 49.9% in 2023. Close collaboration with industry partners and developing an industry-relevant curriculum have played a critical role in this achievement. Furthermore, SMK Negeri 1 Godean also equips students with entrepreneurial skills, increasing graduates pursuing entrepreneurship from 1.6% in 2021 to 9.3% in 2023.